DOUBLE-OBJECT CONSTRUCTIONS IN INDONESIAN: A SYNTACTIC STUDY - Nasrullah, Riki; Budiman, Arip; Kosim, Abdul (Journal of Education for The Language and Literature of Indonesia, 2023)
This paper explores the different types of double-object sentences in Indonesian. This study aims to identify the types of double object constructions based on syntactic behavior, word categories of verb-accompanying constituents, and the verb's form at the construction center. Double object constructions in Indonesian can be divided into two types: double object constructions with double FN constituents (type 1) and double object constructions with combined FN constituents (type 2). The difference between the two types is seen in verb form, syntactic behavior, and the category of verb-accompanying constituents. In terms of verb form, type 1 constructions have verbs ending in -kan and -i, while type 2 does not. In terms of syntactic behavior, type 1 constructions come from single sentences. They can be fixed into other forms by changing the verb and using prepositions "for" and "to" as adverbial function markers in the last constituent. In contrast, type 2 constructions come from broader sentences, so their verb-accompanying constituents form a construction. In terms of the verb-accompanying constituent filler category, type 1 double object constructions only involve nouns as the second filler of the verb-accompanying constituent. In contrast, in type 2 double object constructions, the categories can be nouns, nouns with verbs, adjectives with adjectives, and prepositional phrases.